Níveis e formas de aplicação de lodo de esgoto na nutrição e crescimento inicial da mamoneira - Souto, Lauter S. [UNESP]; Silva, Luciana M. Da [UNESP]; Lobo, Thomaz F. [UNESP]; Fernandes, Dirceu M. [UNESP]; Lacerda, Nilda B. De (Departamento de Engenharia Agrícola - UFCG, 2021)
This research had the purpose of evaluating the effect of forms of application and levels of sewage sludge in the production of dry matter and the macronutrient accumulation in castor bean plants. The experimental study was performed in a 5 x 5 factorial randomized block design, with four replications. The sewage sludge obtained from the Station of Treatment of Sewage ETE-SABESP- in Jundiaí, São Paulo was applied on the surface, incorporated to 25, 50, 75 and 100% of the soil volume during a period of 50 days of crep development in amounts corresponding to 5, 10, 20, 40 and 80 Mg ha-1, (wet-basis. The experimental unit was made up of pots with 4dm3 of sample of a Nitossol Red eutrophic. For the production of dry matter and the accumulation of N, K, Ca, Mg and S in castor bean plant, there was no significant interaction between added levels of sewage sludge and application forms. The application forms significantly increased the macronutrients accumulation and the production of dry matter in castor bean plants.

Este trabalho engloba o propósito de se avaliar o efeito de formas de aplicação e níveis de lodo de esgoto na produção de fitomassa seca e acúmulo de macronutrientes em plantas de mamoneira. O delineamento experimental foi em blocos ao acaso, em esquema fatorial 5 x 5, com quatro repetições. Aplicou-se o lodo de esgoto proveniente da Estação de Tratamento de Esgotos ETE-SABESP-Jundiaí, São Paulo, na superfície, incorporado em 25, 50, 75 e 100% ao volume de solo, durante o período de 50 dias de desenvolvimento da cultura, nas quantidades correspondentes a 5, 10, 20, 40 e 80 Mg ha-1, base úmida. A unidade experimental foi constituída por vasos com 4dm3 de amostra de um Nitossolo Vermelho eutrófico. Para produção de fitomassa seca e acúmulo de N, K, Ca, Mg e S por planta de mamona não houve interação significativa de níveis de lodo de esgoto adicionados e formas de aplicação. As formas de aplicação aumentaram, de maneira significativa, o acúmulo de macronutrientes e produção de fitomassa seca nas plantas de mamona.
Level and forms of application of sewage sludge in the nutrition and growth of castor bean
Keywords: urban residue; nutrient; Ricinus communis; resíduos urbanos; nutrientes; Ricinus communis